2019
DOI: 10.1021/jacs.9b01952
|View full text |Cite|
|
Sign up to set email alerts
|

Iridium-Catalyzed Asymmetric Borylation of Unactivated Methylene C(sp3)–H Bonds

Abstract: Herein, we show the highly enantioselective borylation of unactivated methylene C(sp3)–H bonds in 2-alkylpyridines and 2-alkyl-1,3-azole derivatives using an iridium-BINOL-based chiral monophosphite catalyst system. Quantum chemical calculations using the artificial force induced reaction (AFIR) method suggested that a monophosphite-Ir-tris(boryl) complex generates a narrow chiral reaction pocket where the differentiation of the enantiotopic methylene C–H bonds is accomplished through an assembly of multiple n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…This resulted in full conversion of substrate in 10 h and the resulting borylated aromatic alkyne was isolated in 75% yield (Scheme 4). We used this protocol with a couple of other aryl borylated bromides (10,11) and the Sonogashira products were obtained in good yields (13,14). Synthesis of 14 was run in a bigger scale (10 g, 31.5 mmol) which shows the robustness of this reaction.…”
Section: -Bromobenzotrifluoride Was Chosen As Our Test Substratementioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in full conversion of substrate in 10 h and the resulting borylated aromatic alkyne was isolated in 75% yield (Scheme 4). We used this protocol with a couple of other aryl borylated bromides (10,11) and the Sonogashira products were obtained in good yields (13,14). Synthesis of 14 was run in a bigger scale (10 g, 31.5 mmol) which shows the robustness of this reaction.…”
Section: -Bromobenzotrifluoride Was Chosen As Our Test Substratementioning
confidence: 99%
“…From one-pot CHB/Sonogashira coupling: the general procedure B was applied bromobenzotrifluoride (279 μL, 450 mg, 2.0 mmol, 1 equiv). The borylation step was carried o HBpin (436 μL, 384 mg, 3.00 mmol, 1.50 equiv) for 3 h. The Sonogashira coupling step was out with phenyl acetylene (242 μL, 225 mg, 2.20 mmol, 1.1 equiv) for 5 h. Gradient chromatography (pentane:dichloromethane 4:1 → pentane:dichloromethane 1:1) furnish desired product as orange yellow oil, which solidified on standing (473 mg, 64% yield, mp 74 3-(Trimethylsilylethynyl)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolane-2-yl)-toluene (13).…”
Section: Analytical Data Of Products 12-25 3-(phenylethynyl)-5-(445mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Sawamura group reported that the chiral monophosphoramidite ligands could promote the borylation of methylene C(sp 3 )—H bonds with moderate enantioselectivities . After an extensive optimization of the catalysts, they disclosed an iridium‐catalyzed asymmetric borylation of unactivated methylene C(sp 3 )—H bonds in 2‐alkylpyridines and 2‐alkylazole derivatives by using the 1,1'‐Bi‐2‐naphthol (BINOL)‐based chiral monophosphite ligand L1 (Scheme ) . Borylation of C(sp 3 )—H bond at γ‐position of the heteroatom in the directing group was accomplished with high site‐selectivity and enantioselectivity.…”
Section: Recent Advancesmentioning
confidence: 99%
“…However, enantioselective functionalization reactions of methylene C(sp 3 ) À Hb onds,w hich are more challenging but also more attractive from as ynthetic point of view,h ave been unsuccessful when using this previously reported catalytic system. Herein, we report directed enantioselective methylene C(sp 3 )ÀHf unctionalization reactions using aC p*Rh III /chiral carboxylic acid (CCA) hybrid catalytic system (Scheme 1c), in which abinaphthyl-based CCAassists the enantioselective cleavage of methylene C(sp 3 ) À Hb onds to construct aC À N bond at the stereocenter.A lthough such directing-groupassisted catalytic CÀHa ctivation with the differentiation of methylene C(sp 3 )ÀHbonds has been intensively studied using palladium and other metal catalysts in recent years,m ost studies have focused on C À Co rC À Bb ond formation reactions, [13][14][15][16][17][18][19] leaving enantioselective C À Nb ond formation reactions barely explored. [16a,b,20, 21] Our investigation into enantioselective methylene CÀH amidation of 8-ethylquinoline 1a using dioxazolone 2a to afford 3aa started with attempting to identify an appropriate CCAunder Cp*Rh III catalysis (Table 1).…”
mentioning
confidence: 99%